The Role of Communication Strategy in Crisis Management within Organizations - Hafsa BENHAMMADA; Zineb BAALOUDJ (Eon)
This study aims to explore the necessity of adopting a purposeful and effective strategy for crisis management within organizations. Sudden crises negatively impact organizations, hinder their development, and cause financial and moral losses that shake their position and image. Therefore, these strategies focus on maintaining their reputation and ensuring continuity in the face of unexpected challenges by making clear and effective decisions to deal with emergencies. By analyzing the crisis and its management and emphasizing the most crucial communication tactics and models used in organizational crisis management, the descriptive-analytical technique was utilized to characterize the phenomena, gather data, and analyze it. The study reached several conclusions, most notably that communication plays a positive role in crisis management through the adoption of effective strategies. It also emphasized that crisis communication must be based on well-founded plans and solid principles to ensure prior preparation for managing crises within organizations.